Simbol Keislaman pada Tradisi Rokat Tase’ dalam Komunikasi pada Masyarakat Desa Nepa, Banyuates-Sampang Madura - Wahyu Ilaihi; Siti Aisah (JURNAL INDO-ISLAMIKA, 2012)
Human uses symbol in its communication activity. The symbol can manifest in verbal and non-verbal things. Original culture of a society defines the way how they communicate and the symbol they use. The society of desa Nepa is not an exception. They have used a symbol in performing their local tradition, Rokat Tase’. The symbol used in Rokat Tase’ is a non-verbal symbol of communication, which is manifested in actions and delivery of foods and goods (sesaji). This article discusses the Tradisi Rokat Tase’ and its meaning within the society of desa Nepa. Using bibliographical and empirical inversitigation, this article argues that the main meaning and aim of that symbol is to pray and hope that God (Allah) protects the society in general and sailors in particular. That is also to prevent the occurrence of disaster and calamity and to ask for prosperity and for abundant fishes from sailing. It also stresses that the meaning of this symbol is reached within society’s interaction process and is agreed by all the parties involved in the interaction.